Pengaruh faktor persepsi terhadap minat penggunaan layanan dompet digital (e-wallet) melalui pendekatan teori technology acceptance model (tam) - Sunarya, Irman Maulida (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to analyze the influence of perception factors on interest in using digital wallet services (e-wallet) through the theory technology acceptance model (TAM) approach. The method in this study is a quantitative method, using survey research on all users of the digital wallet application (e-wallet) as the object of research. Data collection is used by distributing questionnaires. The research sample was selected using purposive sampling in order to obtain 246 respondents. The data testing method is instrument test with validity test and reliability test. Validity test using AMOS SEM and Reliability Test using SPSS25. The data analysis method uses SEM with AMOS software. The direct relationship shows that the results of the study of Perceived Usefulness, Perceived Eae of Use, Perceived Trust, Social Influence, Promotion have a positive effect on Behavioral Intention and Use Behavior, and Behavioral Intention has a positive effect on Use Behavior.